1968
DOI: 10.1128/am.16.8.1134-1136.1968
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tolerance of Streptomycetes to Sodium Chloride as a Taxonomic Aid

Abstract: A survey was made of the NaCl tolerance of approximately 1,300 Streptomyces strains belonging to 313 species. The growth medium of the organisms was supplemented with a graded series of NaCl concentrations (4, 7, 10, and 13%). Only 1.8% of the species could not tolerate 4% NaCl; 26.9% could grow at a maximum of 4%; 49.7% could tolerate a maximum of 7%; 18.8% could grow at a maximum of 10%; and only 2.8% could tolerate 13% NaCl. In evaluating the relationships of NaCl tolerance to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The salinity tolerance of actinobacteria depended upon the species and strain of the actinobacteria, as well as the NaCl concentration. For example, Tresner et al [71] found that 1300 Streptomyces strains exhibited different degrees of salinity tolerance (at 4% up to 13% NaCl), which varied according to species and strain. Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salinity tolerance of actinobacteria depended upon the species and strain of the actinobacteria, as well as the NaCl concentration. For example, Tresner et al [71] found that 1300 Streptomyces strains exhibited different degrees of salinity tolerance (at 4% up to 13% NaCl), which varied according to species and strain. Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…PGPA39 [72] and S. rochei SM [70] were tolerant of NaCl concentrations at up to 6 and 20%, respectively. Generally, previous studies reported that the drought, salinity, and pH levels of soil are important factors for microbial grow and survival [70][71][72][73]. Therefore, tolerance to drought, salinity, and pH should be the criteria for selection for microbial utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature range for growth was 30-45°C with optimum at 35°C. The strain exhibited salt tolerance up to 12 % with the optimum level at 7% NaCl; hence, the strain could be placed in the intermediate salt tolerance group 35 Table 5. The strain VLS-2 could also produce enzymes like L-asparaginase, glutaminase, amylase, caseinase and pectinase.…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…In addition to siderophore production, other biochemical characteristics of the selected R7 and F8 actinobacterial isolates were determined in this study, namely protease [46], chitinase [47], amylase [48], volatile compounds production [49], osmotic pressure tolerance [50] and HCN production [51].…”
Section: Biochemical Characterization Of Selected Actinomycetes Isolatesmentioning
confidence: 99%